Acupuncture in Temporomandibular Disorders Painful Symptomatology: An Evidence-Based Case Report - Dietrich, Lia; Rodrigues, Igor Vinícius Santos; Assis Costa, Marcelo Dias Moreira de; Carvalho, Roberta Furtado; Silva, Gisele Rodrigues da (European Journal of Dentistry, 2020)
Temporomandibular dysfunction (TMD) is complex and multifactorial. Its etiology involves various factors, such as malocclusion, psychological patterns, parafunctional habits, and the temporomandibular joint anatomy. Symptoms include myofascial pain, joint clicking, mouth opening limitation, headaches, earaches, and neck pain, comprising one of the greatest causes of nondental pain. Acupuncture has been used to treat these conditions by acting locally both in muscle relaxation and pain management as well as reaching physical, mental, and emotional balance. The aim of this study is to present a brief literature review reporting the efficacy of acupuncture on TMDs and a case report in which the painful symptomatology of TMD was treated with a systemic protocol, based on scientific evidence and concepts of traditional Chinese medicine. Acupuncture may be a complementary treatment for TMD, and in this case report, it eliminated the patient’s painful symptomatology.
Keywords: acupuncture; case report; tempormandibular dysfunction; traditional Chinese medicine